METHOD OF SOLVING SYSTEMS OF LINEAR ALGEBRAIC EQUATIONS IN THE DISTRIBUTED CALCULATING ENVIRONMENT - Glazok, Оlexiy М. (Proceedings of National Aviation University, 2010)
The method of numerical solving of systems of linear algebraic equations produced by the tasks of aerodynamics and hydrodynamics is offered in the paper. The method makes use of the auxiliary function, a value of which is the measure of misclosure of the achieved approximate solution. Proposed a modification of the method suitable for the use in the distributed computing environment.